A new strain of Volutella citrinella with nematode predation and nematicidal activity, isolated from the cysts of potato cyst nematodes in China - Xinyue Zhang (BMC, 2021)
Abstract Background Plant parasitic nematodes (PPNs) are responsible for causing many plant diseases and are extremely difficult to control at present. Currently, due to the negative effects of chemical agents on the environment and human health, the development of new biological pesticides has become an important part of plant nematode control. Nematophagous fungi refers to a class of fungi that kill plant nematodes. Notably, a large number of nematophagous fungi resources remain to be studied. The objective of our study was to use in vitro screening to identify nematophagous fungi and select strains that were highly active against nematodes, providing a primary research for the development and utilization of new nematophagous fungi. Results A new nematophagous fungal strain (GUCC2219) was isolated from cysts of possibly Globodera spp. and Heterodera spp., identified as Volutella citrinella. The hyphae of V. citrinella produced ring structures of variable size and exhibited predatory and nematicidal activity. The hyphal predation rates (in vitro) against three species of nematodes, Aphelenchoides besseyi, Bursaphelenchus xylophilus, and Ditylenchus destructor, averaged 59.45, 33.35, and 50.95%, respectively, while the fermentation broth produced by the fungus exhibited mortality rates of 100, 100, and 55.63%, respectively, after 72 h. Conclusion V. citrinella is a new strain with nematophagous properties, which are a novel discovery. At the same time, this is the first report of nematicidal and nematode predation activity in the genus Volutella.